The Equilibrium Function as an Indicator of Symmetry of Functional Status of Arm Wrestlers - Dmitriy Nicolaevich Chernogorov; Yury Alexandrovich Matveyev; Anton Aleksandrovich Bezzubov (Jan Długosz University in Częstochowa, 2019)
The article is devoted to the study of asymmetry in physical development of arm wrestling athletes at the stage of sports perfection. It presents the results of a pedagogical experiment with the use of static motor-cognitive tests and stabilometry in the detection of asymmetry and proves the effectiveness of the developed system of physical training, based on the achieved improvements of the indicators of equilibrium function of arm wrestlers compared to the standard training system.